2023
DOI: 10.1007/s00011-023-01798-w
|View full text |Cite
|
Sign up to set email alerts
|

A suitable model to investigate acute neurological consequences of coronavirus infection

Jordane Pimenta,
Bruna Da Silva Oliveira,
Anna Luiza Diniz Lima
et al.

Abstract: Objective and design:The present study aimed to investigate the neurochemical and behavioral effects of the acute consequences after coronavirus infection through a murine model. Material:Wild type C57 BL/6 mice were infected intranasally (i.n) with the murine coronavirus 3 (MHV-3). Methods:Mice were submitted to behavioral tests. Euthanasia was performed on the fth day after infection (5 dpi), and the brain tissue was subjected to plaque assays for viral titration, synaptosome, ELISA, histopathological and im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Previous findings from our research group demonstrated that synaptosomes from MHV-3 infected mice have increased glutamate release and intracellular calcium levels (Pimenta et al, 2023). In the current model, MHV-A59-infected female mice also had significant glutamate release and increased intracellular Ca 2+ levels in the hippocampus at 30-dpi.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Previous findings from our research group demonstrated that synaptosomes from MHV-3 infected mice have increased glutamate release and intracellular calcium levels (Pimenta et al, 2023). In the current model, MHV-A59-infected female mice also had significant glutamate release and increased intracellular Ca 2+ levels in the hippocampus at 30-dpi.…”
Section: Discussionmentioning
confidence: 80%
“…Neuromuscular dysfunction is also an important symptom related to COVID-19 (Rossi et al, 2023). At 16 dpi, both female MHV-A59-infected mice displayed a significant decrease in the forelimb and for all limbs grip force compared with mock controls (Fig.…”
Section: Mhv-a59-infected Mice Display Behavioral and Cognitive Alter...mentioning
confidence: 94%
See 3 more Smart Citations